2013
DOI: 10.1093/brain/awt321
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in patients with single, large-scale mitochondrial DNA deletions

Abstract: Single, large-scale deletions of mitochondrial DNA are an important cause of mitochondrial disease, with a broad phenotypic spectrum. Grady et al. report that disease severity and progression are correlated with the size of the deletion, its location within the genome, and the deletion heteroplasmy level in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 59 publications
4
70
3
Order By: Relevance
“…We have studied a limited number of patients in detail and, except for 1 patient, all had a CPEO phenotype. Previous studies from our cohort have used statistical modeling to demonstrate that a variety of outcome measures such as age at onset of symptoms and progression of disease burden, as measured by the Newcastle Mitochondrial Disease Adult Scale, are significantly correlated ( p  < 0.05) with the size of the deletion, the mtDNA deletion level in skeletal muscle, and the position of the mtDNA deletion within the genome 16. With this new information about the presence of different biochemical profiles associated with different deletions, it will be of interest to determine whether there is any link between the biochemical defect and the clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have studied a limited number of patients in detail and, except for 1 patient, all had a CPEO phenotype. Previous studies from our cohort have used statistical modeling to demonstrate that a variety of outcome measures such as age at onset of symptoms and progression of disease burden, as measured by the Newcastle Mitochondrial Disease Adult Scale, are significantly correlated ( p  < 0.05) with the size of the deletion, the mtDNA deletion level in skeletal muscle, and the position of the mtDNA deletion within the genome 16. With this new information about the presence of different biochemical profiles associated with different deletions, it will be of interest to determine whether there is any link between the biochemical defect and the clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Larger mtDNA deletions have been associated with more severe disease and earlier disease onset 15, 16, 17, 18, 19. Whereas a highly significant,20 significant,15, 16, 21, 22 weak,18, 23 or no24 correlation has been reported between the percentage of COX‐deficient fibers and the degree of mtDNA heteroplasmy, most studies found no correlation between the biochemical defects and the nature of the deletion (the number of protein‐encoding genes and the complexes affected by the deletion) or deletion size alone 4, 15, 20, 22, 25. Interestingly, a higher proportion of COX‐deficient ragged‐red fibers was found in patients with deletions encompassing the 3 mtDNA‐encoded COX genes,26, 27 whereas an isolated complex I deficiency was reported in patients with smaller mtDNA deletions removing only complex I genes 26…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies also suggest a correlation among deletion size, heteroplasmy, and clinical severity (Grady et al, 2014).…”
Section: Deletionsmentioning
confidence: 99%
“…Nevertheless, some clinical features are more common in certain genotypes. Thus, for example, central nervous system (CNS) involvement is common in the m.3243A>G and m.8344A>G point mutations,5 but relatively rare in patients with single mtDNA deletions 6…”
mentioning
confidence: 99%